Asnaf Zakat Menurut Muhammad Abduh dan Muhammad Rasyid Ridha - Nurul Jannah (Transformatif, 2022)
This article discusses the concept of zakat funds in the fii sabilillah type based on the views of the mufassir, in which this type is not specified which groups are entitled to receive zakat in this type. So from all the gaps of opinion between mufassir, this article is made to analyze the meaning of fii sabilillah and interpret it to the contemporary era. This research method uses a qualitative descriptive type approach with an analytical method, which is the main reference book is the book of tafsir al-Manar by Muhammad Abduh and Muhammad Rasyid Rida. So from the results of the views of Muhammad Abduh and Muhammad Rasyid Rida in their tafsir, it can be concluded that the zakat group type fii sabilillah can be interpreted in a broad sense, namely fii sabilillah can be used for the general benefit. In their tafsir, Muhammad Abduh and Muhammad Rayid Rida shifted their understanding of the provision of zakat funds for the fii sabilillah group which had been carried out so far, was given for the public interest, not for people in need due to disaster